DIFFERENTIATION OF TETRAPOD COMMUNITIES AND SOME ASPECTS OF BIOTIC EVENTS IN THE EARLY TRIASSIC OF EASTERN EUROPE - Shishkin M.A.; Sennikov A.G.; Novikov I.V.; Ilyina N.V. (My University, 2006)
The patterns of spatial differentiation of the Early Mesozoic terrestrial biota in Eastern Europe and Australia-Tasmania demonstrate that the tetrapod faunal recovery following the Permian extinction was characterized by both global and regional heterogeneity. Local distinctions observed in the development of Early Triassic tetrapod assemblages of European Russia allow the recognition of the following realms: (1) the central and northern regions of the East European Platform (Moscow-Mezen Syncline) and the Timan-North Ural Region; (2) the southern Fore-Urals, including the Obshchii Syrt Plateau; and (3) the southern regions of the East European Platform (the slope of the Voronezh Anticline). Climatic conditions at the initial stage of the development of local communities were characterized by an increase in aridity and seasonal contrasts of climate. Therefore, terrestrial assemblages mostly concentrated in the aquatic and coastal biotopes. Accordingly, vertebrate assemblages of the region were dominated everywhere by aquatic amphibians and semiaquatic reptiles, while the accompanying palynomorph assemblages show the predominance of hygrophilous vegetation indicative of swampy mangrove setting. With respect to amphibians, a peak of local biogeographic differentiation falls on the onset of the Early Triassic and, in the case of reptiles, on the end of this time span. This change conforms to the increasing role of reptiles in the overall taxonomic diversity with time. Among the three main biogeographic units of the region, the Southern Fore-Ural Realm is distinguished by the maintenance of distinct faunal links with Gondwanan regions. The Southern Realm shows a connection with the Germanic Basin and more western Euramerican areas, which is documented for the Late Olenekian and occurred under influence of coastal marine conditions.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая